The Characteristics of Banyuwangi Bilingual Tourism Publication: Strategy or Inaccuracy in Translation? - Rian Wahidi; Wulan Wangi; Wiwin Indiarti (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2021)
This research aims to 1) categorize cultural terms with the theory of translation and culture, 2) analyze translation strategies with the theory of translation strategies and their roles and 3) assess the level of accuracy in translation of cultural terms. The method used is descriptive qualitative. The data in this research are 149 cultural terms, 44 data in the form of words and 105 data in the form of phrases. Data are obtained by documentation, questionnaires and in-depth interview. The results of the research found 19 data of arts, 4 data of clotings, 21 data of culture materials, 52 data of ecology, 39 data of socio-culture and 14 data of society. The translation strategy applied in translating cultural terms are 48 pure borrowing, 15 subtraction, 13 synonym, 6 transposition, structural addition and cultural equivalent respectively 5 data, 1 semantic addition and 1 descriptive equivalent. It is also found the using of couplet strategy, pure borrowing+transposition 40 data, transposition+structural addition 5 data, transposition+semantic addition 5 data, pure borrowing+structural addition and synonym+structural addition 2 data each and pure borrowing+descriptive equivalent 1 data. The role of the translation strategy in producing accurate translations, pure borrowing strategy gave very positive impact on the accuracy of the translation. Meanwhile the less accuracies and inaccuracies occured in translation caused by the using of subtraction strategies, inappropriate synonym strategies, and semantic-addition strategy. The translation accuracy of cultural terms in the Visitor's Guide Book: Majestic Banyuwangi is qualified high level of text accuracy. The accurate translations are 133 data (89,26%), less accurate translations are 14 data (9,4%) and 2 data (1,34%) are inaccurate translations. It can be concluded that the translation resulted is accurate based on the using of translation strategies. They are pure borrowing, structural addition, transposition+structural addition, pure borrowing+structural addition, synonym+structural addition, descriptive equivalent, pure borrowing+descriptive equivalent. It means that Banyuwangi bilingual tourism publication is translated accurately by using those seven strategies.